Summing up : the science of reviewing research - Light, Richard (Harvard University Press, 1984)
An engaging readable, and well-illustrated account of the current art of combining information from several studies. A much-needed book--interesting, readable, attractively presented, practical. Light and Pillemer show an exemplary, nondoctrinaire catholic that I much admire, as well as a willingness to get deep into their, our, and others' experiences as reviewers in order to learn the lessons these experiences teach. Their book is therefore more comprehensive and practical than most books on methods. Astute and wonderfully lucid, Summing Up will be a treasure for inexperienced researchers and contains messages for many experienced ones as well. The book goes beyond techniques for boiling down multiple studies to a single summary "effect size" showing how qualitative information from the original studies improves interpretation.